The Influence of Leadership Style and Teamwork on Work Stress at Bekasi City Police - Irfana, Tungga; Chairunisa, Ririn; Diana, Tungga (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Job stress is a critical aspect that needs to be considered, considering the level of pressure and challenges in the dynamic police environment. High levels of stress can result in decreased welfare, mental health and productivity of members, which in turn can affect the quality of police services. Leadership style and teamwork are considered factors that can influence work stress levels. Good leadership can provide clear direction, support and empower members, while strong teamwork creates a positive and collaborative work environment. Therefore, a deep understanding of how leadership styles and teamwork contribute to job stress levels is essential for designing effective management strategies. The purpose of this research is to find out how leadership style and teamwork influence the work stress of members at the Bekasi City Police. The sampling technique used in this research was saturated sampling. The sample used in this research were members of the HR department of the Bekasi City Police with a sample size of 35 members as respondents. The variables used in this research are Leadership Style (X1), Teamwork (X2) and Work Stress (Y). This research is a type of quantitative research whose data processing uses SPSS version 17. Using multiple linear regression analysis methods, normality tests, descriptive tests, hypothesis tests and f tests (simultaneous). The results of this research show that the Leadership Style variable (X1) has a significant effect on the Work Stress variable (Y), the Teamwork variable (X2) has a positive effect on Work Stress (Y). So, it can be concluded that there is a positive influence between Leadership Style (X1) and Teamwork (X2) together on Job Stress (Y).